Treatment patterns, survival, and hospitalization in adult patients with acute lymphoblastic leukemia: an observational cohort study using SEER Medicare data. Issue 8 (3rd July 2019) - Danese, Mark D.; Katz, Aaron; Cetin, Karynsa; Chia, Victoria; Gleeson, Michelle L.; Kelsh, Michael; Griffiths, Robert I.
Abstract: There is little evidence about whether additional risk stratification for adult patients with acute lymphoblastic leukemia age 65 and older is warranted. Using the Surveillance, Epidemiology, and End Results data linked to Medicare claims, we examined the effects of age, comorbid conditions, and mobility limitations on treatment and survival in a cohort of 795 patients diagnosed with ALL between 1 January 2000 and 31 December 2009. In the cohort, 54% received chemotherapy within the first 90 days, of whom 74% were hospitalized during the first chemotherapy administration. Unadjusted median survival was 172 days (95% CI = 244–379) for the overall cohort, 325 days (95% CI = 244–379) for those age 65–69, but only 59 days (95% CI = 45–76) for those age ≥80. In multivariate analyses, older age groups (70–74, 75–79, and ≥80) and comorbidity score ≥2 were independently associated with poorer survival. Treatment and outcomes vary considerably among subgroups of older patients suggesting that further risk stratification may be useful.